EKSISTENSI SANGGAR SEKINTANG DAYO DALAM SENI PERTUNJUKAN DI SUNGAI KAMBANG KOTA JAMBI - Henvi Ginia Putri; Anak Agung Istri Agung Citrawati; Hardi; Eva Riyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research discusses the existence of Sanggar Sekintang Dayo in performing arts at Sungai Kambang, Jambi City. The purpose of this study is to determine the continuity of Sanggar Sekintang Dayo’s artistic activities in performing arts, as well as the supporting and inhibiting factors that influence its existence. This research used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation involving the leader of the studio, trainers, members, and the surrounding community. The results of the study show that the existence of Sanggar Sekintang Dayo can still be seen through routine training activities, involvement in various art performances, and participation in cultural events. The studio also utilizes social media as a means of introducing its activities and performances to the wider community. Supporting factors for the studio’s existence include community support, the role of leaders and trainers, and the interest of the younger generation in dance arts. Meanwhile, the inhibiting factors are limited facilities and funding in supporting the studio’s activities.